Improving Communication With Low-Income Women Using Today's Technology. - Cibulka, Nancy J.; Fischer, Harry W.; Fischer, Anna J. (Online Journal of Issues in Nursing, 2012)
The authors of this article examine reasons for missed appointments and preferences for appointment reminders among inner city obstetrics and gynecology clinic patients having a high missed-appointment rate. Sixty low-income women, including African Americans, Caucasians, and members of other ethnic groups, with a mean age of 27 years, were interviewed by telephone. The most frequently cited reason for missed appointments was forgetfulness. Almost all study participants indicated that they would like a text message reminder of upcoming appointments along with telephone and/or postal letter reminders. In this article the authors review the literature addressing both missed appointments and trends in mobile technologies, report their study of missed appointments, and conclude that text messaging appointment reminders can decrease missed appointments among young, low-income women.